Kombinasi Kascing dan POC Air Kelapa Meningkatkan Pertumbuhan Bibit Pinang Betara (Areca catechu L.) di Tanah Ultisol: Combination of Vermicompost and Coconut Water Liquid Organic Fertilizer Improves the Growth of Pinang Betara (Areca catechu L.) Seedlings in Ultisol Soil - Rindiani Arsamsi, Nolisa; Salman, Salmita; Ernita; Nursamsul Kustiawan; Mulyani, Sri; Adelina Maryanti (DINAMIKA PERTANIAN, 2026)
Background: Red Yellow Podzolic (Ultisol) soil has low fertility, which inhibits the growth of Betara areca nut (Areca catechu L.) seedlings. The combination of vermicompost and coconut water liquid organic fertilizer (LOF) has the potential to improve this condition. Objective: This study aimed to evaluate the main and interactive effects of vermicompost and coconut water LOF on the growth of Betara areca nut seedlings in Ultisol soil. Methods: The research employed a 4×4 factorial completely randomized design with three replicates. The first factor was vermicompost dosage (0, 50, 100, and 150 g/polybag), and the second factor was coconut water LOF concentration (0%, 25%, 50%, and 75%). Observed parameters included plant height, number of leaf sheaths, stem diameter, leaf area, leaf sheath length, fresh weight, dry weight, root length, and root volume. Results: The interaction between vermicompost and coconut water LOF significantly affected plant height, number of leaf sheaths, stem diameter, leaf area, leaf sheath length, and root volume. The best treatment was the combination of 150 g/polybag vermicompost and 75% coconut water LOF (K3P3). Individually, vermicompost at 150 g/polybag significantly affected all parameters except interaction, while coconut water LOF at 75% concentration significantly affected all parameters except dry weight. Conclusions: The combination of vermicompost and coconut water LOF significantly enhances the vegetative growth of Betara areca nut seedlings, with the K3P3 treatment being the most effective